O protagonismo dos leigos à luz do Vaticano II, no Episcopado de Dom José Freire de Oliveira Neto, na Diocese de Mossoró-RN (1984-2004). - Silva, José Roberto da (2025)
This research uses a qualitative approach, with a descriptive and explanatory nature, and is based on documentary analysis that generated critical analyses in order to obtain a better understanding of the phenomenon under study. Having as a corpus the historical testimonies of people who experienced the pastorship of Dom José Freire de Oliveira Neto, this thesis research has the general objective of recovering the historical memory of the aforementioned Pastor based on interviews and testimonies of some people published in local newspapers (when the death of the Bishop Emeritus of Mossoró was reported), between January 10 and 12, 2012. To this end, this work is developed with the guiding methodology called Content Analysis, by Laurence Bardin, aimed at analyzing the data obtained. Among the Content Analysis techniques conceived by the author, Categorical Analysis is the one that interests this research. Considering the reports of the interviewees, data were obtained that, in comparison with the theoretical framework, lent themselves to the research problem. In pursuit of the proposed objective, data collection was carried out through semi-structured interviews with 24 people, including family members, lay people, nuns and priests. Drawing on the study of collective memory, undertaken by Halbwachs (2006), and other theorists who contributed to the development of this research, such as Bosi (1994), Bosi (2003), Cavalcanti (1992), Matos (2002), Matos (2011), Hoornaert (1984), Boff (1990), Boff (1994), Rossi (2010) remembering the figure of Dom José Freire consisted of a process of remembering a historical subject who marked the history of the Diocese of Mossoró itself, whose evocation of the memories of the interviewees, or of the people who spoke out in some local newspaper reports, supported the construction of the historical memory of the memorable Pastor. In addition to the data from the historical reports obtained, the historical collection presented in this thesis proved to be relevant for preserving the memory and legacy of Dom José Freire, as the memories evoked by the interviewees proved to be incisive for the clarity of the remembered past, broadening horizons for a better understanding of individual memories that, intertwined with collective memory, provided support for the constitution of Dom Freire's historical memory.